Clinical features and outcomes of Ewing sarcoma in infants: A single center case series from India - Badira Cheriyalinkal Parambil; Maya Prasad; Venkata Rama Mohan Gollamudi; Ajay Puri; Sajid Qureshi; Siddhartha Laskar; Nehal Khanna; Jifmi Jose Manjali; Mukta Ramadwar; Bharat Rekhi; Vasundhara Patil; Akshay Baheti; et al. (Elsevier, 2024)
Background: Infantile Ewing Sarcoma (ES) is an extremely rare disease with comparable outcomes on contemporary protocols. There is a paucity of data from India. Methods: Infants with proven ES diagnosed between January 2012 and December 2020 were retrospectively analyzed. The staging was performed using positron emission tomography-computerized tomography scan. Treated infants were administered weight-based chemotherapy. The local control was with surgery and/or radiotherapy. Results: There were 10 infants with ES with a male-to-female ratio of 2.3:1. The majority had extraosseous (90 %, n = 9) or axial primary (50 %, n = 5). Five patients with localized disease received treatment. Two died during induction chemotherapy (sepsis-1, cause unknown-1), and 3 are alive with no evidence of disease at a median follow-up of 8 years (range: 4-9). Two episodes of complicated febrile neutropenia were reported in 5 treated infants. Conclusions: ES in infants is rare and predominantly extraosseous with axial primary. Treated infants with non-metastatic disease tolerated chemotherapy well with good outcomes.